Qualitative Path Analysis Of The Correlation Between Teacher Job Embeddedness And Holistic Student Learning Outcomes At Religious Madrasah - Muhes, Ahmad Dzofron Abiyyu Tsaqib Muhes; Aimah, Siti (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Qualitative Path Analysis Of The Correlation Between Teacher Job Embeddedness And Holistic Student Learning Outcomes At Religious Madrasah This study aims to analyze the correlation and path of influence of teachers' Job Embeddedness on the quality of students' holistic learning outcomes in madrasas with religious values. A qualitative case study at Darussalam Tulungagung Integrated Junior High School collected data through participant observation, in-depth interviews, and documentation studies. The data were analyzed interactively referring to the Miles, Huberman, and Saldaña models through three stages: data condensation with thematic coding, presentation of data in the form of qualitative path diagrams, and conclusion drawing and verification. The findings reveal a unique configuration of Job Embeddedness that is transformed into religious values: Fit becomes spiritual harmony, Links becomes an Islamic ukhuwah network, and Sacrifice as a moral responsibility. Religious values act as a critical mediator that transforms work attachment from mere psychological retention to spiritual-collective commitment. Implicitly, such teacher attachment significantly shapes the holistic learning quality of students, including the formation of character and spiritual values, in addition to contributing to cognitive aspects.